Natural alternatives for reducing bacterial biofilms in food industry - Almeida, Rodolfo Nunes; Universidade Federal do Ceará (2017)
Of the microorganisms often found in biofilms, bacteria are the predominant group. In the food industry, pathogenic biofilms considered of great importance in the context of food safety and public health, arousing the interest of researches, highlighting the use of essential oils due to their antimicrobial properties, with the purpose of making sanitizers that have less impact compared to chemical sanitizers that may eventually transfer chemical waste to food. The aim of this review was to present the process of forming bacterial biofilms in the food industry and to suggest some natural alternatives for its reduction. It is concluded that biofilm formation is natural and the search for alternative ways to reduce the chemical impact contaminating the environment and food, leads to natural solutions. This demonstrate the ability to act against various microorganisms and can be incorporated into sanitizers, detergents and infinite other possibilities